Identification of Novel Microsatellite Markers Flanking the SMN1 and SMN2 Duplicated Region and Inclusion Into a Single-Tube Tridecaplex Panel for Haplotype-Based Preimplantation Genetic Testing of Spinal Muscular Atrophy - Zhao, Mingjue; Lian, Mulias; Cheah, Felicia S.H.; Tan, Arnold S.C.; Agarwal, Anupriya; Chong, Samuel S. (Frontiers in Genetics, 2019)
Preimplantation genetic testing for the monogenic disorder (PGT-M) spinal muscular atrophy (SMA) is significantly improved by supplementation of SMN1 deletion detection with marker-based linkage analysis. To expand the availability of informative markers for PGT-M of SMA, we identified novel non-duplicated and highly polymorphic microsatellite markers closely flanking the SMN1 and SMN2 duplicated region. Six of the novel markers within 0.5 Mb of the 1.7 Mb duplicated region containing SMN1 and SMN2 (SMA6863, SMA6873, SMA6877, SMA7093, SMA7115, and SMA7120) and seven established markers (D5S1417, D5S1413, D5S1370, D5S1408, D5S610, D5S1999, and D5S637), all with predicted high heterozygosity values, were selected and optimized in a tridecaplex PCR panel, and their polymorphism indices were determined in two populations. Observed marker heterozygosities in the Chinese and Caucasian populations ranged from 0.54 to 0.86, and 98.4% of genotyped individuals (185 of 188) were heterozygous for ≥2 markers on either side of SMN1. The marker panel was evaluated for disease haplotype phasing using single cells from two parent–child trios after whole-genome amplification, and applied to a clinical IVF (in vitro fertilization) PGT-M cycle in an at-risk couple, in parallel with SMN1 deletion detection. Both direct and indirect test methods determined that none of five tested embryos were at risk for SMA, with haplotype analysis further identifying one embryo as unaffected and four as carriers. Fresh transfer of the unaffected embryo did not lead to implantation, but subsequent frozen-thaw transfer of a carrier embryo produced a pregnancy, with fetal genotype confirmed by amniocentesis, and a live birth at term.